Fungal Seed Endophyte FZT214 Improves Dysphania ambrosioides Cd Tolerance Throughout Different Developmental Stages - Parmar, Shobhika; Sharma, Vijay K.; Li, Tao; Tang, Wenting; Li, Haiyan (Frontiers in Microbiology, 2022)
Phytoremediation is a promising remediation method of heavy metal (HM)–contaminated soils. However, lower HM tolerance of metal accumulator inhibits its practical application and effects. The current study was aimed to illustrate the role of fungal seed endophyte (FZT214) in improving Dysphania ambrosioides Cd tolerance during different developmental stages under various Cd stresses (5, 15, 30 mg kg–1) by pot experiments. The results showed that FZT214 significantly (p < 0.05) improved the host plant’s growth at the flowering and fruiting stage in most of the treatment, while at the growing stage the increase was less (p > 0.05). The seed yield was also improved (p < 0.05) in the FZT214-inoculated plants (E+) and induced early flowering was observed. Moreover, the inoculation also positively affected total chlorophyll content, antioxidant process, and lipid peroxidation in most of the treatments throughout three developmental stages. Not all but in most cases, IAA and GA were more in E+ plants while JA was more in the E− plants (non-inoculated plants) during three developmental stages. The results suggested that the colonization of FZT214 to the D. ambrosioides might trigger multiple and comprehensive protective strategies against Cd stress, which mainly include activation of the dilution effects, induced biochemical changes to overcome damage from Cd toxicity, and alteration of the endogenous phytohormones. FZT214 can find competent application in the future to improve the growth of other crop plants.